2002
DOI: 10.1177/089198870201500103
|View full text |Cite
|
Sign up to set email alerts
|

The "Time and Change" Test: An Appropriate Method to Detect Cognitive Decline in the Elderly

Abstract: The Time and Change (T&C) test is an easy and time-saving test validated for the detection of dementia. Our aim was to determine how geriatric features like depression, disability, and comorbidity are able to influence the result of the T&C and, consequently, to decide whether it could be a reliable screening test for cognitive impairment in the elderly. A total of 220 participants (mean age = 75.8+/-9.6 years, 63.7% females) underwent the T&C, Mini-Mental State Examination, and the Clock Drawing Test; Activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The Time and Change (T&C) test was developed by Inouye et al [11] to assess (i) how well a patient understands time and (ii) the ability of the patient to calculate using money. Several studies have found that the T&C test allows direct assessment of two important activities of daily living and supplements the testing of calculation, conceptualization, and visuospatial cognitive domains irrespective of race and education [11-13]. …”
Section: Introductionmentioning
confidence: 99%
“…The Time and Change (T&C) test was developed by Inouye et al [11] to assess (i) how well a patient understands time and (ii) the ability of the patient to calculate using money. Several studies have found that the T&C test allows direct assessment of two important activities of daily living and supplements the testing of calculation, conceptualization, and visuospatial cognitive domains irrespective of race and education [11-13]. …”
Section: Introductionmentioning
confidence: 99%
“…Challenges that face the ageing population include poor motivation in self care (Mussi et al 2002), dissociative states that include depression and in some cases suicidal ideation (Rubin andHewstone 1998, De Leo et al 2001), loneliness (Bruce et al 2007), emotional distress (Scott et al 2001) and impaired quality of life (Hassell et al 2006). Such challenges indicate the more negative outcomes arising from the enormous social transformation that an ageing population may experience upon entering a later stage of life.…”
Section: Literature Review Occupation In Later Lifementioning
confidence: 99%
“…After all, the same study identified darifenacin as being five times more constipating than oxybutynin, and 10 times more so than placebo, a side effect that few patients are likely to brush aside. While the Name‐Face Association Test possesses good test–retest reliability and ecological validity, it does not appear to possess the same validity as other tests, such as the Time and Change test, in detecting dementia and cognitive impairment in elderly people (10,11). Cognitive testing should include a comprehensive analysis of the aforementioned tasks in order to best identify the effects of OAB agents on all aspects of cognition, rather than simply the most salient features.…”
mentioning
confidence: 99%